Uma proposta de regulador automático de tensão microcontrolado para geradores síncronos isolados - Alves, Guilherme Henrique (2016)
The excitation control systems in synchronous machines must very quickly detect changes caused by load increase on the isolated generator and act on the excitation system in a rapid and efficient way in order to maintain terminal voltage at optimal desired levels. Unlike other works related with this area which used analog-based electronic circuits, this controller can in many case be built utilizing microcontrolled technology which is more efficient and flexible to implement different control strategies, as well as having a low cost of production. The approach of this research consists in a proposal to apply an automatic excitation controller, utilizing a PID control loop, including manual adjustments and monitorings of terminal voltage and stator temperature of the machine. It employs a PIC16F877A microcontroller from the Microchip Technology Company. The results obtained through practical tests in laboratory with a direct online start of induction motors (1 and 2 HP) on a 2 kVA generator show that the controller acts to recover the terminal voltage to the adopted setpoint in a reduced time. Finally, the results were also compared to the time of response provided from another well-known automatic voltage regulator found in the market, in order to prove the good control performance of this project.